PENGARUH KEPEMILIKAN SERTIFIKASI ISO 14001, KINERJA LINGKUNGAN, DAN KOMPETISI PADA PENGUNGKAPAN EMISI KARBON - Evodia Jeniffer Meiliana Puspa; Dian Purnama Sari (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study aims to analyze the effects of International Organization for Standardization (ISO) 14001 certification, environmental performance, and industry competition on carbon emission disclosure. Research Methodology: The research data were obtained from the annual and sustainability reports of energy and transportation companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2024. Data were analyzed using statistical methods, including multiple regression. Results: The results indicate that ISO 14001 certification, environmental performance, and industry competition positively affect carbon emission disclosure. Conclusions: This study shows that ISO 14001 certification, environmental performance, and industry competition positively affect carbon emission disclosure. Limitations: The presence of numerous outliers in the data is a limitation of this study. Another limitation is that more than 50% of the sample companies did not have a Program Penilaian Peringkat Kinerja Perusahaan (PROPER) rating during the observation period. Contributions: This research is expected to increase companies' commitment to managing the environmental impacts of their operations not just through ISO 14001 certification but also through ongoing efforts to improve environmental performance. Furthermore, increased transparency in carbon emissions disclosure is expected to boost investor confidence and strengthen corporate legitimacy in the capital market.